Cross-border B2C e-commerce to Greater China and the role of logistics: a literature review. Issue 9 (2nd October 2017) - Giuffrida, Maria; Mangiaracina, Riccardo; Perego, Alessandro; Tumino, Angela
Abstract : Purpose: This paper reviews scientific publications in the field of logistics underlying cross-border e-commerce (CBEC) to China. A focus on the role played in this complex process by other countries of the Greater China is carried out. The purpose of this paper is to outline directions for future research to encourage CBEC development. Design/methodology/approach: The review is based on 32 papers published from 2002 to 2016 in international peer-reviewed journals or proceedings of international conferences, retrieved from bibliographic databases and science search engines. Findings: CBEC to China is gaining increasing interest, as shown by the rising amount of publications from 2013 onwards. Within these contributions, however, studies specifically investigating the relation between logistics and e-commerce, commonly acknowledged as critical, seem to lack. Many contributions are descriptive and do not provide specific insights on how to manage the complexities of CBEC logistics in this region. Stemming from the review, a set of possible development areas are identified, including distribution network design, i.e. deciding how to shape the CBEC distribution structure, and logistics outsourcing, i.e. determining whether to manage logistics activities in-house or through third parties. Originality/value: To the extent of the authors' knowledge, this paper is the first one to classify the existing body of knowledge on logistics supporting CBEC. Its main contribution is the critical identification of current research gaps and the proposal of key themes for future research. From a managerial perspective, it helps export and logistics managers identify the key challenges of managing CBEC logistics to Greater China.